2017
DOI: 10.1371/journal.pone.0179634
|View full text |Cite
|
Sign up to set email alerts
|

Serum variations of anti-mullerian hormone and total testosterone with aging in healthy adult Iranian men: A population-based study

Abstract: BackgroundLiterature proves anti-mullerian hormone (AMH) and total testosterone (TT) as two important reproductive hormones in male development, however evidence regarding age variations of these hormones is lacking.AimsTo estimate the normal serum AMH values and to assess the age-specific TT levels in men aged 30–70, we conducted the present population-based study.MethodsA total of 831 healthy eligible men, aged 30–70 years, were recruited from Tehran Lipid and Glucose study cohort. Centiles for AMH were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
(71 reference statements)
2
9
2
1
Order By: Relevance
“…The regression was not significant between phthalate metabolite concentrations and AMH in the WHOLE population. The main effect of age on serum and semen AMH level has been documented [ 23 ] and our results show that the level of AMH at the age above 60 is the lowest, as reported in the cross-sectional study [ 24 ]. As a result, we further divided the population into different age groups and did find significant regression in some age groups.…”
Section: Discussionsupporting
confidence: 86%
“…The regression was not significant between phthalate metabolite concentrations and AMH in the WHOLE population. The main effect of age on serum and semen AMH level has been documented [ 23 ] and our results show that the level of AMH at the age above 60 is the lowest, as reported in the cross-sectional study [ 24 ]. As a result, we further divided the population into different age groups and did find significant regression in some age groups.…”
Section: Discussionsupporting
confidence: 86%
“…Testes, hormone production, and spermatogenesis undergo senescence as a man ages 98. Johnson et al 99 identified an age-related decrease in Sertoli cell number; consistent with this, AMH, as a marker of immature Sertoli cells, was also found to be reduced with increasing age36100101 and negatively correlated with FSH and LH, which indicates that decreased AMH levels as a man ages represent age-related reduced Sertoli cell function.…”
Section: Associations Between Serum Amh and Disorders Related To Malementioning
confidence: 85%
“…AMH measurement have clinical advantage over measurements of other markers of ovarian aging, such as inhibin B, estradiol and follicle-stimulating hormone (FSH), which are all menstrual cycle dependent and mark only late ongoing process of primordial follicle pool depletion [ 20 ]. We have shown that serum AMH may serve as marker for testicular function after induced toxicity, whereas other groups demonstrated age dependent serum AMH reduction that may serve as marker for testicular aging and age-related reducing of testicular function [ 22 24 ]. Percentiles of AMH levels in females were determined according to AMH-nomograms of Tehrani et al [ 25 ].…”
Section: Resultsmentioning
confidence: 99%